2015
DOI: 10.1016/j.urology.2015.02.029
|View full text |Cite
|
Sign up to set email alerts
|

Chronological Urodynamic Evaluation of Changing Bladder and Urethral Functions After Robot-assisted Radical Prostatectomy

Abstract: Purpose: The current tumor-node-metastasis (TNM) classification system has been used for many years.The prognosis of patients with metastatic prostate cancer (mPC) treated using primary androgen deprivation therapy (PADT) was analyzed according to the TNM classification.Methods: A total of 5,618 cases with lymph node metastases only (N1M0), non-regional lymph node metastasis (M1a), bone metastasis (M1b), and distant metastasis (M1c) were selected from the Japanese Study Group of Prostate Cancer database. Overa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
89
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(91 citation statements)
references
References 34 publications
0
89
1
Order By: Relevance
“…From 3 months after RP, the proportion of patients with UUI and post‐void leakage did not change compared with that before RP probably because of the disappearance of postoperative reactions, such as acute inflammation. SUI after RP was reported to be mainly caused by urethral sphincter dysfunction . This study showed some patients who complained about post‐void leakage pre‐ and post‐RP; therefore, post‐void leakage should also be taken into consideration when evaluating UI after RP.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…From 3 months after RP, the proportion of patients with UUI and post‐void leakage did not change compared with that before RP probably because of the disappearance of postoperative reactions, such as acute inflammation. SUI after RP was reported to be mainly caused by urethral sphincter dysfunction . This study showed some patients who complained about post‐void leakage pre‐ and post‐RP; therefore, post‐void leakage should also be taken into consideration when evaluating UI after RP.…”
Section: Discussionmentioning
confidence: 88%
“…The types of UI reported after RP were mainly stress UI (SUI) and partially urge UI (UUI), but daily pad use and 24‐h pad weight test cannot distinguish between the two types. Urodynamic studies are useful for evaluating the pattern of UI; however, it is invasive and complicated . Various questionnaires are also used for the subjective evaluation of UI: the Expanded Prostate Cancer Index Composite is used to evaluate QOL, including the urinary status, of patients with localized prostate cancer patients; the International Consultation on Incontinence Questionnaire‐Short Form (ICIQ‐SF) is a simple questionnaire for evaluating UI after RP, including a subjective UI evaluation and the pattern of UI .…”
Section: Introductionmentioning
confidence: 99%
“…Urinary incontinence (UI) can occur in men after prostate surgery of benign or malignant conditions, secondary to bladder dysfunction and/or ISD arising from iatrogenic injury to the urethral sphincter muscle or its innervation …”
Section: Resultsmentioning
confidence: 99%
“…Chronological urodynamic evaluation of patients with PPI after RARP revealed that urethral sphincter and bladder function worsen immediately after RARP and recover over time [63]. In one small cohort study, 20.6% of patients had UI 1 year after RARP.…”
Section: Urodynamic Evaluation Of Men With Lower Urinary Tract Symptomentioning
confidence: 99%